2012
DOI: 10.1002/app.38042
|View full text |Cite
|
Sign up to set email alerts
|

Plasticized and nanofilled poly(lactic acid)‐based cast films: Effect of plasticizer and organoclay on processability and final properties

Abstract: PLA-based nanocomposites filled with the commercial organomodified montmorillonite Dellite 43B (D43B) and containing acetyl tri-n-butyl citrate (ATBC) as plasticizer were prepared by extrusion in a pilot-scale twin-screw extruder and melt casted into flexible films. A preliminary investigation was carried out in a laboratory batch mixer by varying blending conditions and addition procedures of the components. Indeed, the method of addition of ATBC and D43B considerably affected thermo-mechanical properties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…When adding 10%wt plasticizer, T g decreases from 60 to 38°C for the PLA‐5/TA while it decreases from 60 to 41°C for the PLA‐8/ATBC. Similar observations have been reported in the literature with ATBC yielding T g values between 45 and 47°C at a content of 10 wt% and between 17 and 38°C at a content of 20 wt% while TA decreases T g from 60°C (neat PLA) to values between 29 to 48°C at a content of 10 wt% and between 21 to 29°C at 20 wt% . Plasticization is typically dependent on the chemical nature of the molecule .…”
Section: Resultssupporting
confidence: 88%
“…When adding 10%wt plasticizer, T g decreases from 60 to 38°C for the PLA‐5/TA while it decreases from 60 to 41°C for the PLA‐8/ATBC. Similar observations have been reported in the literature with ATBC yielding T g values between 45 and 47°C at a content of 10 wt% and between 17 and 38°C at a content of 20 wt% while TA decreases T g from 60°C (neat PLA) to values between 29 to 48°C at a content of 10 wt% and between 21 to 29°C at 20 wt% . Plasticization is typically dependent on the chemical nature of the molecule .…”
Section: Resultssupporting
confidence: 88%
“…Interestingly, if the plasticization was carried out in the presence of poly(Butylene adipate-co-terephthalate) (PBAT) as polymeric additive, a preferential migration of the acetyl tributyl citrate in the PBAT phase was observed [36] suggesting the necessity of selecting a plasticizer on the basis of its preferential affinity with the PLA matrix. [32,33,[38][39][40] As both rigid and flexible packaging is generally used for liquid or pasty cosmetic, the barrier properties of PLA-based formulations must be particularly high. Usually barrier properties can be improved thanks to the use of inorganic additives.…”
Section: Poly(lactic Acid)mentioning
confidence: 99%
“…Among the inorganic additives, layered silicates, such as montmorillonite (MMT), appear to be effective fillers to improve the overall performances of PLA system even at low concentration (1-5 wt %) [37]. However, to reach this improvement, a high degree of clay dispersion that highly depends on the adopted preparation method, and on the compatibility between the polymer matrix and the clay is needed [38,39]. Jorda-Beneyto et al [40,41] used two organo-modified clays for food contact applications to produce hydrophobically-modified montmorillonite, to obtain better compatibility between the biopolymer and the filler (nanoclay).…”
Section: Poly(lactic Acid)mentioning
confidence: 99%
“…The plasticizer has a synergistic effect: it improves the processability and flexibility and at the same time it can facilitate the dispersion of the CNs. Citrates plasticizers have been investigated in literature; thanks to their ester groups, they have a very good affinity with the PLA matrix and favor the CNs dispersion [41][42][43]. However, it has been demonstrated that another very effective plasticizer for the dispersion of CNs is the poly(ethylene glycol) (PEG) [32,34,44,45].…”
Section: Introductionmentioning
confidence: 99%